Analysis Of Service Quality At Se'indonesia Brand Fast Food Restaurants In Bandar Lampung - Tina Miniawati Barusman Virgawenda; Romarito Pandiangan (International Journal of Education, Vocational and Social Science, 2026)
The competition in the fast food restaurant industry in Indonesia, particularly in the city of Bandar Lampung, requires every business actor to provide optimal service quality in order to maintain customer satisfaction and loyalty. Se'Indonesia fast food restaurants, as one of the culinary business operators, face challenges in maintaining service consistency amid increasing consumer expectations regarding speed, accuracy, comfort, and the attitude of service staff. The problem addressed in this study focuses on the quality of service provided and the extent to which the service has met consumer expectations. The purpose of this study is to analyze and describe the service quality at Se'Indonesia brand fast food restaurants in Bandar Lampung. The method used in this research is a descriptive method with a qualitative approach. Data were collected through interviews, observations, and documentation. The collected data were analyzed then inductively to understand the actual conditions of the services provided by the restaurant based on consumer perceptions and field observations. The results and discussion indicate that the service quality at the Se'Indonesia fast-food restaurant in Bandar Lampung is generally assessed as good, characterized by fast, friendly, and consistent service that is able to meet customer expectations. Most customers experience positive confirmation between their expectations and the actual service performance, although constraints still occur during peak hours, which affects service speed. Efforts to improve service quality have encompassed all SERVQUAL dimensions through improvements in facilities, order accuracy, service speed, employee professionalism, and empathetic attitudes. The integrated implementation of the tangibles, reliability, responsiveness, assurance, and empathy dimensions has been proven to have a positive impact on customer satisfaction and is in line with the SERVQUAL model.